Opportunities for Using Smartphones in the Digital Era to Facilitate Students in Learning Sociology in High Schools - Qodr, Taufiq Subhanul; Efendi, Agus; Musadad, Akhmad Arif (Universitas Pendidikan Ganesha, 2021)
The development of information technology that encourages smartphones in various lives thus opens up opportunities for the use of smartphones in teaching and learning activities. However, teachers have not been able to maximize the use of smartphones to support students' ability to understand learning materials. This certainly does not provide a good learning experience for students, so it is necessary to improve the learning system. This study was conducted to identify opportunities for using smartphones to make it easier for students to learn, especially in understanding sociology learning materials in high school. This type of research is descriptive qualitative research. The research subjects were social studies students of class X SMA with a total of 149 students. Data collection methods in this study were surveys and interviews using questionnaires and interview guidelines as research instruments. Data analysis was carried out in four stages: data collection, data reduction, data presentation, and conclusion. This study indicates that there is an excellent opportunity for the use of smartphones in the digital era in the learning process, especially in sociology in high school. The opportunity is the implementation of game-based mobile learning or Mobile Game-Based Learning (MGBL). It can be seen that the use of smartphones by students is most dominantly used to play games, with a percentage of 32.90%. Thus, Mobile Game-Based Learning (MGBL) as a learning medium is an opportunity to use smartphones to make it easier for students to learn sociology because it encourages students to be more active, creative, and innovative in the learning process. This study concludes that Mobile Game-Based Learning (MGBL) is an excellent opportunity for the use of smartphones in the digital era to make it easier for students to learn sociology in high school.